Oreocharis ninglangensis, a showy new species of Gesneriaceae from northwestern Yunnan in China - Chen, Wen-Hong; Chen, Run-Zheng; Möller, Michael; Wen, Kai; Shui, Yu-Min (Phytotaxa, 2016)
A new species of Oreocharis (Gesneriaceae) from northwestern Yunnan in China is described and illustrated. The new species, Oreocharis ninglangensis, is most similar to O. delavayi, but it can be easily distinguished from it by conspicuous red stripes inside the corolla mouth and by the finely bullate leaf surface in the latter.